Clinical Outcomes of Patients With B-Cell Non-Hodgkin Lymphoma in Real-World Settings: Findings From the Hemato-Oncology Latin America Observational Registry Study. (29th April 2022) - Pavlovsky, Miguel; Cubero, Daniel; Agreda-Vásquez, Gladys Patricia; Enrico, Alicia; Mela-Osorio, Maria J.; San Sebastián, Jorge Armenta; Fogliatto, Laura; Ovilla, Roberto; Avendano, Oscar; Machnicki, Gerardo; Barreyro, Paula; Trufelli, Damila; et al.
Abstract : PURPOSE: Real-world evidence on non-Hodgkin lymphoma (NHL) management in Latin America is currently lacking. The objective of this study was to describe treatment characteristics and outcomes of NHL in Latin America. METHODS: A total of 2, 967 patients with NHL with aggressive and indolent subtypes, including diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL), mantle-cell lymphoma (MCL), and mucosa-associated lymphoid tissue (MALT) lymphoma, with incident or prevalent diagnosis between 2006 and 2015, were retrospectively identified using clinical charts registered in the Hemato-Oncology Latin America Observational Registry. Associations between treatment regimen and age at diagnosis with clinical outcomes within each subtype were estimated using Cox proportional hazard regression. RESULTS: Most patients with NHL received 1L chemoimmunotherapy, most commonly cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) with/without rituximab. Five-year survival rates were higher for MALT lymphoma (90.8%) and FL (87.6%) versus DLBCL (69.0%) and MCL (57.1%), with variations between countries. The median overall survival from first relapse for patients with DLBCL was 6.6 years, with lower risk of death for those diagnosed at age < 65 years (hazard ratio = 0.732; P = .0161). Patients achieved a longer median progression-free survival with 1L rituximab-CHOP (R-CHOP) versus CHOP or rituximab, cyclophosphamide, vincristine, and prednisone (RCVP) (7.7 v 3.0 or 1.8 years, respectively). Use of regimens other than R-CHOP was associated with a higher risk of death/progression for patients with DLBCL (rituximab, ifosfamide, carboplatin, and etoposide/ifosfamide, carboplatin, and etoposide) and FL (CHOP). There was no relationship between treatment prescribed and age at diagnosis with outcomes from first/second relapse in DLBCL and FL. CONCLUSION: Differences in treatment outcomes between NHL subtypes were observed, reflecting variations in NHL management and barriers to treatment access in Latin America. These data provide necessary evidence to understand NHL management in this region and highlight the need to improve treatment outcomes for these patients.